Dual Detection of Temperature And Chiral Amino Acid Using Triphenylamine‐Based Fluorescent Probes. Issue 40 (25th October 2022) - Tu, Yajing; Cao, Jian; Zhang, Meijuan; Liu, Mingming; Huang, Cuiping; Li, Yanan; Wang, Chuanxiao
Abstract: Accuracy measurement of temperature is important in day‐to‐day life and scientific research. Chiral amino acids play an irreplaceable role in medicine, biochemistry, and other fields; however, the polarity solvents do easily disturb hydrogen bond formation between chiral amino acids and fluorescence probe. Herein, a fluorescent probe Tap‐S, using triphenylamine as fluorophore, is synthesized for dual detection of temperature and enantiomers of chiral amino acids in polarity aqueous solution. The fluorescence emission of Tap‐S to the temperature has a good response in the mixed solvent of methanol and glycerin over a wide temperature range (−45 to 50 °C). The gradient thermosensitivity, accuracy and reversibility of Tap‐S to the temperature in our strategy are achieved. Tap‐S can emit yellow fluorescence in the high‐viscosity mixed solution. By taking advantage of the viscosity measurement, the restricted intramolecular rotation mechanism of Tap‐S's fluorescence emission was effectively clarified. Furthermore, the potential use of Tap‐S to selective detect L‐phenylalanine of chiral amino acids has been successfully executed in the polarity aqueous solution at the room temperature (25 °C). The complex of Tap‐S and L‐phenylalanine can inhibit the rotation of the single bond of Tap‐S inducing the fluorescence emission. This work provides a novel strategy for the studies on not only the detection of temperature but also the enantiomers of chiral amino acids. Abstract : A fluorescent probe Tap‐S, using triphenylamine as fluorophore, is synthesized for dual detection of temperature and enantiomers of chiral amino acids in polarity aqueous solution. The fluorescence emission of Tap‐S to the temperature has a good response in the mixed solvent of methanol and glycerin over a wide temperature range (‐45 to 50 °C). The potential use of Tap‐S to selective detect L‐phenylalanine of chiral amino acids has been successfully executed in the polarity aqueous solution at the room temperature (25 °C).